Association between Hyposensitivity of C-fiber Afferents at The Proximal Urethra and Storage/voiding Dysfunction in Female Patients with Detrusor Overactivity - Ichiyanagi, Osamu; Nishimoto, Ken-ichi; Nagaoka, Akira; Naito, Sei; Yagi, Mayu; Ushijima, Masaki; Kato, Tomoyuki; Tsuchiya, Norihiko (Urology Journal, 2020)
Purpose: We examined the associations between urethral sensation and storage/voiding function in female patients with detrusor overactivity (DO) by measuring urethral current perception threshold (CPT). Materials and Methods: We retrospectively investigated the medical records of 27 consecutive patients with lower urinary tract symptoms who underwent cystometry, uroflowmetry (UFM), and urethral CPT tests from 2000 to 2015. Patients were classified into 2 groups: with/without DO. Seven DO-negative cases were selected as normal controls on cystometrogram (CMG) matching the inclusion criteria: bladder compliance ?12.5 mL/cmH2O, volume <275 mL at first sensation, and no comorbidities possibly influencing micturition. Finally, 17 patients were included. Urethral CPT was evaluated with intraurethral square-wave impulses at 3 Hz to stimulate C-fibers. Urethral loss coefficient (LC), reflecting urethral resistance during voiding, was calculated by curve-fitting a mathematical model to a UFM waveform. Results: Urge incontinence (UI) was observed in 7 DO-positive patients, but not in those with normal CMG. Urethral CPT and LC were significantly higher in patients with DO than in those with normal CMG. Median urethral CPT significantly increased in patients with both DO and UI than in those without these symptoms (p<0.005). CPT values were correlated with the volume at first sensation (?=0.53, p<0.05) and LC (?=0.59, p<0.05). LC was not calculated in 3 cases due to poor curve-fitting. Conclusions: In females, urethral C-fiber afferents may become hyposensitive as the detrusor becomes overactive with UI in the storage phase. During voiding, C-fiber hyposensitivity may relate to increased functional resistance of the urethra to urine outflow.